Evaluation instruments to verify originality of research in thesis - Fuentes, Milagros (2019)
The integrity of researchers is a problem since time immemorial; there was always misconduct in the investigation, such as fraud, forgery and plagiarism. Today it is more noticeable, because the knowledge society, thanks to technology, has allowed the development of instruments to verify originality in research. This research aimed to analyze some instruments that can be applied in the evaluation of the master's and doctoral theses of the Graduate School of the Andean University Nestor Cáceres Velásquez. Applying the qualitative approach; using physical instruments such as "codes of honor" where sanctions are established for misconduct and digital instruments such as "software" that allow verifying the originality of the studies. It was observed that the application of these tools has served to reduce scientific malpractice. According to several studies and tests carried out on the systems, of the great variety of software, the ones with the best qualifications are: Urkund with an efficiency of 73% being in the appropriate range, while Turnitin 67% being in the range poor, this is due to the amount of files to compare a job, the more databases, the better the application.